The comparison of the three assays for determination of fecal calprotectin in inflammatory bowel disease - Osredkar, Joško (Array, 2021)
Fecal calprotectin is a biomarker for monitoring inflammatory bowel disease (IBD) activity. Our aim, therefore, was to evaluate two new assays, the point of care test Quantum Blue and the Liaison Calprotectin with respect to the Calprest, commonly used assay, and to determine their performance for IBD diagnosis.We included 73 prospective patients with IBD. Fecal calprotectin was measured and analysed with the routine Calprest assay and two recently introduced assays, the Quantum Blue and the Liaison Calprotectin. Furthermore, we compared the results by Bland and Altman analysis, and Passing-Bablok regression.We observed no difference in median calprotectin values obtained by the Calprest (94.6 µg/g, 95%CI 66.5 to 166.1) and Liaison assay (101.0 µg/g, 95%CI 48.1 to 180.1) whereas significantly higher concentrations were obtained with the Quantum Blue assay (240.0 µg/g, 95%CI 119.9 to 353.2). The mean absolute and relative difference between the Calprest and Quantum Blue methods was statistically significant (- 162.3 µg/g and - 143.1%). Mean absolute difference between the Calprest and Liaison calprotectin methods was positive (2.2 µg/g). The agreement between assays revealed that Quantum Blue and Calprest have fair agreement with Kappa coefficient of 0.38 (95%CI 0.26 to 0.51). Liaison Calprotectin and Calprest revealed moderate agreement with a weak Kappa coefficient of 0.47 (95%CI 0.32 to 0.62).Clinicians should be aware of these differences between the assays and avoid comparison of their respective results.